Potential mechanisms of exercise for relieving inflammatory pain: a literature review of animal studies - Wu, Minmin; Song, Wenjing; Zhang, Mei; Teng, Lili; Tang, Qiang; Zhu, Luwen (Frontiers in Aging Neuroscience, 2024)
Inflammatory pain (IP) is one of the most prevalent and intractable human conditions, and it leads to progressive dysfunction and reduced quality of life. Additionally, IP is incredibly challenging to treat successfully with drugs or surgery. The development of IP is complex and multifactorial, and peripheral and central sensitization may influence chronicity and treatment resistance in IP. Understanding the mechanisms underlying IP is vital for developing novel therapies. Strong evidence suggests that exercise can be a first-line relief for patients with IP during rehabilitation. However, the mechanisms through which exercise improves IP remain unclear. Here, we reviewed the current animal experimental evidence for an exercise intervention in IP and proposed biological mechanisms for the effects of synaptic plasticity in the anterior cingulate cortex, endocannabinoids, spinal dorsal horn excitability balance, immune cell polarization balance, cytokines, and glial cells. This information will contribute to basic science and strengthen the scientific basis for exercise therapy prescriptions for IP in clinical practice.